A novel system for continuous protein refolding and on-line capture by expanded bed adsorption - Ferré, Henrik (Cold Spring Harbor Laboratory Press, 2005)
A novel two-step protein refolding strategy has been developed, where continuous renaturation-bydilution is followed by direct capture on an expanded bed adsorption (EBA) column. The performance of the overall process was tested on a N-terminally tagged version of human β(2)-microglobulin (HAT-hβ(2)m) both at analytical, small, and preparative scale. In a single scalable operation, extracted and denatured inclusion body proteins from Escherichia coli were continuously diluted into refolding buffer, using a short pipe reactor, allowing for a defined retention and refolding time, and then fed directly to an EBA column, where the protein was captured, washed, and finally eluted as soluble folded protein. Not only was the eluted protein in a correctly folded state, the purity of the HAThβ(2)m was increased from 34% to 94%, and the product was concentrated sevenfold. The yield of the overall process was 45%, and the product loss was primarily a consequence of the refolding reaction rather than the EBA step. Full biological activity of HAT-hβ(2)m was demonstrated after removal of the HAT-tag. In contrast to batch refolding, a continuous refolding strategy allows the conditions to be controlled and maintained throughout the process, irrespective of the batch size; i.e., it is readily scalable. Furthermore, the procedure is fast and tolerant toward aggregate formation, a common complication of in vitro protein refolding. In conclusion, this system represents a novel approach to small and preparative scale protein refolding, which should be applicable to many other proteins.